Analysis of the Needs of Concrete Iron Material Availability in The Work of the Chhazan Space Through the Eoq Approach Method (Case study: Project for Building a Bank Indonesia Representative Office for Gorontalo Province) - Stella Junus; Muh. Yasser Arafat; Dwi Noviani; Sofiyah H. Sabaya (AIBPM Publisher, 2018)
PT. Housing Development (Persero). tbk or PT. PP is a state-owned company engaged in construction and investment with experience in building prestigious buildings, infrastructure, properties and Engineering Procurement Construction (EPC) for more than 60 years. The purpose of this study is to get the right technique in obtaining the number of material orders (lot size) that can form the minimum cost and to get the minimum total cost (total cost) of material inventories. This research method is the Eoq Method Approach. The results showed that D16 mm Concrete Iron the number of economic installations amounted to 38, 995.59 Kg and inventory costs of Rp. 76,821.32, concrete iron D25 mm the number of economical orders amounted to 11,264.90 Kg and the total cost of Rp 22,190.54, and concrete iron D32 mm the number of economic orders was 11,646.90 Kg and the total cost of Rp 20,636.83. Keywords: EOQ, Materials, Supplies